Incidence of Infection by the Hepatitis A Virus Diagnosed in the City of Maracaibo, State of Zulia, Venezuela - Luciana Costa León; Leticia Porto Espinoza; Francisca Monsalve Castillo; Diana Callejas Valero; Jesús Estévez; María Elena Castellanos Sánchez (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2010)
Hepatitis A virus (HAV) infection continues to be a public health problem in developing countries. The aim of this study was to determine incidence of the hepatitis A virus infection in a population from Maracaibo, Venezuela. From January, 2004 until December, 2007, this study was carried out on 1056 individuals, whose ages were between 1-60 years (average ± DS: 27.48 ± 5.24 years), coming from the Maracaibo and San Francisco municipalities, Venezuela. The IgM antibody against HAV was determined by the ELISA technique. The overall incidence was 26.6%. The North, South, East and West areas of the Maracaibo Municipality and the San Francisco Municipality in the city of Maracaibo showed incidences of 73 (35.1%), 76 (28%), 66 (24.3%), 35 (20.3%) and 31(23.3%), respectively. The highest incidences were observed in females under 20 years (47.3%) and males under 10 years (53.7%). The most frequent clinical sign was jaundice in 95.7% of patients. Deficient sanitary conditions and hygiene habits seemed to be the main risk factors in spreading HAV infection.